THE ACHIEVEMENT OF EXCLUSIVE BREASTFEEDING FACTORS IN THE WORKING ARCA OF BETUNG PUBLIC HEALTH CENTER, OI REGENCY - Wandira, Ayu; Aquari, Bina; Rahmadhani, Sendy Pratiwi; Minata, Fika (Jurnal Kesehatan Saintika Meditory, 2025)
Achieving exclusive breastfeeding is one of the efforts to improve the fulfillment of nutritional needs so that it can improve the nutritional status of infants and children. The purpose of this study was to detemine the relationship between Perception of Inadequate Breastfeeding (PIB), the role of health workers, and type of childbirth with the achievement of Exclusive Breastfeeding in the working arca of the Betung Public Health Center, OI Regency in 2024. The study used an analytical survey method and a crosssectional approach. The population in this study were 285 mothers in the working area of the Betung Public Health Center who had babies aged more than 6-12 month & sample was 74 respondents taken using a purposive sampling technique. The primary data collected using a questionnaire and analized using the Chi Square test. The results of the study obtained that 46 (62.2%) respondents provided Exclusive Breastfeeding, PIB was insufficient 24 (32.4%), the role of officers had no influential 16 (21.6%), and 15 (20.3%) respondents childbirth by caesarean section. Based on the results of statistical tests, it is known that there was a relationship between PIB (p value 0.006), the role of health workers (p value 0.002) and the type of childbirth (p value 0.004) with the achievement of exclusive breastfeeding.Keywords: Exclusive Breastfeeding, Perception of Inadequate Breastfeeding (P1B), role of health worker